DESKRIPSI MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 2 AMPANA KOTA DALAM PEMBELAJARAN MATEMATIKA - Dunggio, Fadlia H.; Nurhayadi, Nurhayadi; Karniman, Tegoeh S. (Universitas Tadulako, 2022)
This study is a research that uses a quantitative approach that aims to describe learning motivation of the 8th grade students of SMP Negeri 2 Ampana City in learning mathematics. The data in this study were collected using a questionnaire sheet with a total of 22 items and measured using a Likert scale, namely (1) strongly disagree, (2) disagree, (3) undecided, (4) strongly agree, (5) strongly disagree, as well as observational data in the form of pictures. The research subjects consisted of 60 grade VIII students drawn from 2 different classes. The results of this study indicate that students' learning motivation in learning mathematics in class VIII of SMP Negeri 2 Ampana Kota has an average of 3.0 and is included in the high category, with the indicator of being diligent in facing the task of getting an average of 3.0 in the high category, the tenacious indicator faces difficulty getting an average of 3.1 in the high category, the indicator showing interest in various problems gets an average of 2.8 in the sufficient category, the indicator prefers to work independently gets an average of 2.9 in the sufficient category, the indicator of getting bored quickly on routine tasks gets an average of 3.2 in the high category, and the indicator can defend opinions rationally gets an average of 2.8 in the moderate category.